A panoramic view of type 4 Kuhn cells, only one of its kind - Prasad, K. C.; Mohiyuddin, Azeem; Swapanthi, M. B.; Harshita, T. R.; Gopinath, Induvarsha; Koneru, Pratyusha; Nallencherry, Mansheer (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
There are different type of pneumatizing air cells in the frontoethmoidal region, as described by Kuhn el all, in this type IV Kuhn cell is that kind of cell which is completely isolated within the frontal sinus, or as Wormald described it as, fronto-ethmoidal cells extending more than 50% of its vertical height of the frontal sinus. In this study we would like to show a macroscopic or panoramic view of type IV Kuhn cell, which was a glorious view while performing an external approach, as there is no literature on type IV Kuhn cell with a panoramic view. Possibly this could be the first of its kind in medical literature. And therefore, this image can be incorporated in various studies for further references.